2010
DOI: 10.1590/s0365-05962010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Padrão dermatoscópico das alopecias cicatriciais causadas por lúpus eritematoso discoide e líquen plano pilar

Abstract: FUNDAMENTOS: A dermatoscopia é método importante de diagnóstico de doenças melanocíticas benignas e malignas. Recentemente, o uso desse método tem demonstrado grande ajuda também no diagnóstico e acompanhamento das alopecias. OBJETIVO: Descrever e demonstrar os achados dermatoscópicos de pacientes com quadros clínicos e histopatológicos de alopecia cicatricial. MÉTODOS: Estudo transversal descritivo em que foram selecionados, pelos achados clínicos e histopatológicos do couro cabeludo, 14 pacientes com alopeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 6 publications
7
32
2
1
Order By: Relevance
“…Lack of follicular ostia is indicative of scarring alopecia5. In addition, in this study, the lack of follicular ostia was frequently observed in cases of scarring alopecia such as DLE, LPP, and PB.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Lack of follicular ostia is indicative of scarring alopecia5. In addition, in this study, the lack of follicular ostia was frequently observed in cases of scarring alopecia such as DLE, LPP, and PB.…”
Section: Discussionsupporting
confidence: 51%
“…However, some of these approaches are invasive and not always available. Dermoscopy was recently introduced as a useful technique for diagnosing various hair and scalp diseases, including AA, TM, androgenic alopecia, TC, DLE, LPP, or inherited hair shaft dystrophies1,2,3,4,5,6. The reports did not emphasize the dermoscopic differences among various forms of alopecia, but focused only on describing the dermoscopic findings of each disease.…”
Section: Introductionmentioning
confidence: 99%
“…These are an expression of melanophages in papillary dermis and indicate incontinentia pigmenti. They are a feature of two scalp diseases, namely LED and LPP, where they assume two different aspects: in LPP, blue-gray dots appear with a ‘target pattern' due to the circular arrangement of melanin around the perifollicular area, sparing the interfollicular area [16], unlike LED, where blue-gray dots follow a speckled pattern indicating an involvement of the interfollicular areas with a sprinkling of melanin in these areas [7,17]. …”
Section: Methodsmentioning
confidence: 99%
“…However, epidemiological history, clinical presentation and dermoscopic findings pointed to the diagnosis of LPP, which was confirmed through histopathology [9,10]. …”
Section: Figmentioning
confidence: 99%